Novel genetic testing model: A collaboration between genetic counselors and nephrology. Issue 4 (21st January 2021) - Amlie‐Wolf, Louise; Baker, Laura; Hiddemen, Olivia; Thomas, Morgan; Burke, Christine; Gluck, Caroline; Zaritsky, Joshua J.; Gripp, Karen W.
Abstract: Many barriers to genetic testing currently exist which delay or prevent diagnosis. These barriers include wait times, staffing, education, and cost. Specialists are able to identify patients with disease that may need genetic testing, but lack the genetics support to facilitate that testing in the most cost, time, and medically effective manner. The Nephrology Division and the Genetic Testing Stewardship Program at Nemours A.I. duPont Hospital for Children created a novel service delivery model in which nephrologists and genetic counselors collaborate in order to highlight their complementary strengths (clinical expertise of nephrologists and genetics and counseling skills of genetic counselors). This collaboration has reduced many barriers to care for our patients. This workflow facilitated the offering of genetic testing to 76 patients, with 86 tests completed over a 20‐month period. Thirty‐two tests were deferred. Twenty‐seven patients received a diagnosis, which lead to a change in their medical management, three of whom were diagnosed by cascade family testing. Forty‐two patients had a negative result and 16 patients had one or more variants of uncertain significance on testing. The inclusion of genetic counselors in the workflow is integral toward choosing the most cost and time effective genetic testing strategy, as well as providing psychosocial support to families. The genetic counselors obtain informed consent, and review genetic test results and recommendations with the patient and their family. The availability of this program to our patients increased access to genetic testing and helps to provide diagnoses and supportive care.